Comparison and detail study of attacks and detection methods for wireless sensor network - Karthik Krishnan, T; Sridevi, S; Bindu, G; Anandan, R (International Journal of Engineering and Technology, 2018)
Wireless sensor network is emanating technology in the field of telecommunications. WSNs can be applied in many fields like machine surveillance, precision agriculture, home automation and intelligent building environments. However the major aspect of WSN is the security as the sensor nodes are limited because of these facing several security threats such as black hole attack, worm hole attack, flooding etc. which is finally affecting the functioning of the whole network. These attacks are maximizing the consumption of power in the node and also it decreases life of the battery. In this paper, we discuss several types of security attacks in wireless sensor networks and also it introduces various intrusion detection systems to detect these attacks and prevent the compromised nodes in the WSN. And also we discuss about the different intrusion detection methods with the help of machine learning algorithms. In future these techniques can be helpful to create a safe and sophisticated network.Â Â